Public Education and Social Citizenship - Potentials and Pitfalls - Ray , Paroma (South Asian Journal of Social Sciences and Humanities, 2020)
In this paper I aim to explore the ideological and practical connections between citizenship and public education. Drawing from Marshall’s social citizenship I will attempt to explore the strands of ideas that facilitate or restrict the growth of social citizenship. The idea of global cosmopolitan citizenship and Deep citizenship will be of special interest to me and I shall attempt to locate the ethics behind them and how it ties up with public education. Questions of justice and equality and rights will be the ethical considerations that would form an undercurrent to my discussion on citizenship and education. Walzer, Agamben and Arendt’s ideas will be important in order to understand these dimensions. I will also attempt to briefly trace the evolution of the concept of mass education and public education and look at both nationalizing as well as globalizing tendencies in its history. While I will be looking at the educational policies of India, I shall focus on only those aspects of education in India that fit the general frame of the debates happening globally. Lastly, I will focus on the specific question of movement of both citizens and non-citizens and its relationship with public education. Given that education takes place over a decade of someone’s life informal movement has significant impact on the breaks and continuity in one’s education and in one’s perception of oneself as a member of a productive community that puts a premium value on education and educational qualifications while allowing for the exploitation of those without an education.